2017
DOI: 10.5194/hess-21-2249-2017
|View full text |Cite
|
Sign up to set email alerts
|

Variation of soil hydraulic properties with alpine grassland degradation in the eastern Tibetan Plateau

Abstract: Abstract. Ecosystems in alpine mountainous regions are vulnerable and easily disturbed by global environmental change. Alpine swamp meadow, a unique grassland type in the eastern Tibetan Plateau that provides important ecosystem services to the upstream and downstream regions of international rivers of Asia and other parts of the world, is undergoing severe degradation, which can dramatically alter soil hydraulic properties and water cycling processes. However, the effects of alpine swamp meadow degradation on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 58 publications
5
23
0
Order By: Relevance
“…In the present study, we observed a sharp decrease in SWC with enhanced degradation (Table 1), which is another major negative influence of degradation on soils, consistent with previous findings (Wang et al, 2009;Yi et al, 2012). It may be because retrogression induces decreases in field capacity and saturated hydraulic conductivity (Pan et al, 2017), which play important positive roles in key hydraulic courses and functions, such as water holding capacity, soil water retention, and infiltration (Fu et al, 2015). Additionally, due to the decline in plant cover, more soil areas are exposed to stronger radiation, which induces an increase in evaporation-reducing SWC (Wang et al, 2009).…”
Section: Variations Of Soil Properties Along the Degradation Gradientsupporting
confidence: 92%
“…In the present study, we observed a sharp decrease in SWC with enhanced degradation (Table 1), which is another major negative influence of degradation on soils, consistent with previous findings (Wang et al, 2009;Yi et al, 2012). It may be because retrogression induces decreases in field capacity and saturated hydraulic conductivity (Pan et al, 2017), which play important positive roles in key hydraulic courses and functions, such as water holding capacity, soil water retention, and infiltration (Fu et al, 2015). Additionally, due to the decline in plant cover, more soil areas are exposed to stronger radiation, which induces an increase in evaporation-reducing SWC (Wang et al, 2009).…”
Section: Variations Of Soil Properties Along the Degradation Gradientsupporting
confidence: 92%
“…Changes in soil particle size and aggregate structure also contribute to soil desiccation. Even in the extremely degraded grasslands that have been reclaimed for conversion into artificial grasslands, there is no significant improvement in water-retention capacity [9]. With an increase in grazing intensity, the soil saturated moisture capacity, the capillary moisture capacity, and the field moisture capacity do not increase linearly; they all increase initially but then decrease, with a peak at the stage of moderate degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The slope of the soil water retention curve (WRC) was also found to be significantly influenced by ρ b (Dexter, 2004a). In addition, soil water-holding capacity and infiltration rate and capacity also exhibited complex responses to variations in ρ b caused by traffic compaction, tillage, topographic variability, or rainfall-induced surface sealing (Assouline, 2004;Mohammadshirazi et al, 2016;Pan et al, 2017;Strudley et al, 2008). It is necessary to relate soil hydraulic properties to ρ b for improved understanding and prediction of water, solute, and gas transport in soil.…”
Section: Introductionmentioning
confidence: 99%